Immune cell topography of head and neck cancer - Muijlwijk, Tara; Nijenhuis, Dennis N L M; Ganzevles, Sonja H; Ekhlas, Fatima; Ballesteros-Merino, Carmen; Peferoen, Laura A N; Bloemena, Elisabeth; Fox, Bernard A; Poell, Jos B; Leemans, C René; Brakenhoff, Ruud H; van de Ven, Rieneke (Journal for immunotherapy of cancer, 2024)
BackgroundApproximately 50% of head and neck squamous cell carcinomas (HNSCC) recur after treatment with curative intent. Immune checkpoint inhibitors are treatment options for recurrent/metastatic HNSCC; however, less than 20% of patients respond. To increase this response rate, it is fundamental to increase our understanding of the spatial tumor immune microenvironment (TIME).MethodsIn total, 53 HNSCC specimens were included. Using a seven-color multiplex immunohistochemistry panel we identified tumor cells, CD163+macrophages, B cells, CD8+T cells, CD4+T helper cells and regulatory T cells (Tregs) in treatment-naive surgical resection specimens (n=29) and biopsies (n=18). To further characterize tumor-infiltrating CD8+T cells, we stained surgical resection specimens (n=12) with a five-color tumor-resident panel including CD103, Ki67, CD8 and pan-cytokeratin. Secretome analysis was performed on matched tumor suspensions (n=11) to measure protein levels.ResultsBased on CD8+T cell infiltrates, we identified four different immunotypes: fully infiltrated, stroma-restricted, immune-excluded, and immune-desert. We found higher cytokine levels in fully infiltrated tumors compared with other immunotypes. While the highest immune infiltrates were observed in the invasive margin for all immune cells, CD163+macrophages and Tregs had the highest tendency to infiltrate the tumor center. Within the tumor center, especially B cells stayed at the tumor stroma, whereas CD163+macrophages, followed by T cells, were more often localized within tumor fields. Also, B cells were found further away from other cells and often formed aggregates while T cells and CD163+macrophages tended to be more closely located to each other. Across resection specimens from various anatomical sites within the head and neck, oral cavity tumors exhibited the highest densities of Tregs. Moreover, the distance from B cells and T cells to tumor cells was shortest in oral cavity squamous cell carcinoma (OCSCC), suggesting more interaction between lymphocytes and tumor cells. Also, the fraction of T cells within 10 µm of CD163+macrophages was lowest in OCSCC, indicating fewer myeloid/T-cell suppressive interactions in OCSCC.ConclusionsWe comprehensively described the TIME of HNSCC using a unique data set of resection specimens. We discovered that the composition, as well as the relative localization of immune cells in the TIME, differed in distinct anatomical sites of the head and neck.